Evolving social values: intersectional analysis of same-sex and interracial couples in magazine advertisements - To, Erica (My University, 2024)
This study used a quantitative content analysis and qualitative image analysis to explore the representation and intersectionality of same-sex and opposite-sex couples with interracial and intraracial couples in advertisements from Canadian Living, Châtelaine, Cosmopolitan, Elle, Men’s Health, Reader’s Digest, and Sports Illustrated magazines between January 2021 to March 2024. Observations collected from a sample of 208 advertisements depicting two or more adults were used to tentatively suggest dominant Canadian social values towards same-sex and interracial couples. Advertisement images were coded for gender, race, the activity depicted, the physical touch between adults, and the presence of children. Results showed that representation of same-sex couples, both interracial and intraracial, was higher than the proportion reported in Canada in 2016. Similarly, the representation of interracial couples, both same-sex and opposite- sex, was higher than the proportion reported in Canada in 2021. These two findings suggest growing acceptance of same-sex relationships and interracial relationships. Interracial couples involving a White female partner occurred far more often than those involving a White male partner, suggesting social disapproval of unions between White women and visible minorities may no longer prevail. However, in advertisements with interracial or intraracial couples, depictions of physical intimacy favoured couples that were of the opposite sex. Advertisements with same-sex couples displaying intimacy were more often intraracial than interracial. Displays of intimacy from same-sex couples were almost exclusively between two women, and no interracial couples were engaged in very intimate touch. Results of the intersectional analysis finds a bias favouring intraracial, opposite-sex couples over both interracial, same-sex couples and interracial, opposite-sex couples unless the couples were engaged in simple touch, conveying friendship over intimacy. These biases suggest social approval of interracial relationships and same-sex relationships as long as they appear superficial or casual and potential social disapproval of relationships that are both interracial and same-sex. Only four advertisements depicted children with couples, and these showed a bias favouring opposite-sex, intraracial couples. The overall results from this study indicate that although there is increased representation of same-sex couples and interracial couples, advertisements may continue to reflect and perpetuate heteronormative and intraracial social values in concepts of relationships and family.
Keywords: interracial couples; intraracial couples; intersectional analysis; media bias